PEMBANGUNAN KEAHLIAN PUBLIC SPEAKING MELALUI KEGITAN KHITOBAH DI PONDOK PESANTREN ASAASUNNAJAAH KESUGIHAN CILACAP - Yusri Wahidah; M. Fatikhun (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2022)
This study aims to determine the public speaking skills development program for students through khitobah activities and to find out the results of khitobah activities on the development of students' public speaking skills. The method used in this research is a qualitative descriptive approach that explains, describes systematically based on the phenomena that occur. Data collection techniques used are observation, interviews, and documentation. Meanwhile, to analyze the researchers used data reduction, data presentation, and drawing conclusions. The results of this study indicate that the program for developing public speaking skills for students is through khitobah activities, namely: first, being the host or MC at the khitobah activity. Second, to be a welcoming speech at the sermon activity. Third, being a speaker at a sermon activity. By frequently participating in sermon activities for students and always practicing and continuing to practice when they become officers at sermon activities, students' public speaking skills can be built. While the results of the sermon activity on the development of students' public speaking skills are: first, students become more confident. Second, the students have the courage to appear in public. Third, be mentally strong. Fourth, mature yourself. Fifth, useful for the future of students.